Women across cultures a global perspective - Burn, Shawn Meghan (New York, NY McGraw Hill LLC, 2023)
The cross-cultural study of women's issues and women's movements, the focus of this book, is fascinating and educational. It tells of women and girls' disadvantage relative to boys and men and how that disadvantage arises from the greater male rights and privilege embedded in cultures, institutions, groups, and minds. Unfortunately, this truth can be disturbing at times. But this book is also uplifting because it is equally about hope, resilience, and the power of people to fight and right social injustices. Throughout the book are many examples of actions to address women's issues and promote gender equality-ranging from the small grassroots effort addressing local women's issues to the use of international law for improving women's status. The global study of women is also about diversity and intersectionality and their importance for understanding the gendered human experience. Gendered discriminations are often heightened by their interaction with other discriminations such as those based on race, class, sexual orientation, age, and gender identity. The experiences and issues of women vary widely based on these and other intersections. Women's experiences as women are also strongly shaped by the particular political, social, and cultural contexts where they live, leading to diversity in women's lives and issues, and in their advocacy and activism. This diversity is true not only in our own country, but also globally. Documenting, studying, and appreciating this variety are hallmarks of global women's and gender studies and one of the major aims of this book. Hope the readers find the global study of women captivating and inspiring. Hope that after reading the book they not only better understand how the world works but that they also feel compelled to do their part for gender equality. Hope that readers will be struck by the scope of gender injustice but equally struck by the scope of women's resistance and the possibilities for change. Hope that the book helps readers better understand and appreciate feminism, diversity, and intersectionality, as they are so often caricatured, ridiculed, and negatively stereotyped. Hope that the book reflects and honors internationally oriented women's and gender studies scholarship and the many women's movements actors and organizations that advocate and serve women"--
Includes bibliographical references and index.
Keywords: Sex discrimination against women -- Cross-cultural studies; Sex role -- Cross-cultural studies; Women's rights -- Cross-cultural studies; Women -- Economic conditions -- Cross-cultural studies; Women -- Social conditions -- Cross-cultural studies